THE EFFECT OF NORDIHYDROGUAIARETIC ACID ON LEUKOTRIENE-C(4) AND PROSTAGLANDIN-E(2) PRODUCTION FOLLOWING DIFFERENT REPERFUSION PERIODS IN RAT-BRAIN AFTER FOREBRAIN ISCHEMIA CORRELATED WITH MORPHOLOGICAL-CHANGES - (:unkn) unknown (CHURCHILL LIVINGSTONE, 1993)
Leukotriene C4 (LTC4) and prostaglandin E2 (PGE2) are the 5-lipoxygenase and cyclooxygenase metabolites of arachidonic acid (AA). They constrict blood vessels and enhance vascular permeability inducing vasogenic edema that may hurt the ischemic penumbra after cerebral ischemia and reperfusion. Nordihydroguaiaretic acid (NDGA) is known as the most potent inhibitor of 5-lipoxygenase in different tissues. Furthermore, it has considerable inhibitory activity against cyclooxygenase. In this study, after developing a global ischemic model in the rat, the levels of LTC4 and PGE2 in the forebrain were measured, following different reperfusion periods after 10 min ischemia including 8 rats for each reperfused group. Sham operations were performed for each corresponding control group (n = 8). AA metabolites were then correlated with neuropathological findings. In the combined reperfused groups both metabolites increased significantly when compared with 10 min, ischemic group (P < 0.05). In the 8 min reperfused group, PGE2 and LTC4 increased significantly compared with each corresponding control group (P < 0.005). These mediators also increased to high levels compared with the 4 min reperfused group (P < 0.05, P < 0.005). PGE2 and LTC4 were reduced significantly at the 15th and 60th min of reperfusion compared with the 8 min reperfused group (P < 0.05, P < 0.005). NDGA (0.1 mg/kg) reduced both metabolites in the 8 min reperfused group significantly (P < 0.05). Brain cortex specimens were taken for light and electromicroscopical investigations. No significant differences were noted between the structural changes in the 4, 8 and 15 min of reperfusion and NDGA administered groups. Widenings of subendothelial spaces around capillaries and degeneration of neurons were seen at the 60th min of reperfusion whereas similar but lesser changes was observed at 60 min in the NDGA-administered animals. In conclusion, NDGA reduced LTC4 as well as PGE2 at a dosage of 0.1 mg/kg following 8 min reperfusion. It may be helpful in protecting the ischemic penumbra in the early min of reperfusion by reducing the formation of both 5-lipoxygenase and cyclooxygenase metabolites.
Keywords: GUINEA-PIG; ARACHIDONIC-ACID; BLOOD-FLOW; GERBIL; INDOMETHACIN; LIPOXYGENASE; INHIBITORS; TISSUE; EDEMA